The Relationship Between Social Support, Physical Activity and Mental Health in University Students - Devira Mamonto; Ali Imron; Veni Fatmawati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Background: Students are a group that is vulnerable to mental health disorders due to academic demands, social adjustment, and the pressure of planning for the future. Factors that are thought to be related to student mental health include social support and physical activity. Objective: This study aims to determine the relationship between social support and physical activity with mental health in students. Methods: This study uses an analytical observational design with a cross-sectional approach. The sample consisted of 224 students selected using purposive sampling. The instruments used were the Multidimensional Scale of Perceived Social Support (MSPSS), the International Physical Activity Questionnaire–Short Form (IPAQ-SF), and the Self Reporting Questionnaire-20 (SRQ-20). Data analysis was performed using univariate and bivariate analysis with the Chi-Square test and multivariate analysis using ordinal regression. Result: The results showed that most students were in the high (29.5%) and moderate (27.7%) mental health disorder categories, with an average score of 9.52 ± 4.39. There is a significant relationship between social support (p=0.000) and physical activity (p=0.000) with students' mental health. Multivariate analysis shows that physical activity is the most influential factor on students' mental health (p=0.000; OR=0.10; 95% CI=0.06–0.17). Conclusion: Social support and physical activity are related to students' mental health, with physical activity being the dominant factor. Increasing physical activity and strengthening social support need to be the focus of promotional and preventive efforts for students' mental health. Suggestion: Further research should focus on physical activity training for students' mental health.